Production of Microcrystalline Cellulose Aerogels by Supercritical Gel Drying, for Water Remediation - Alessandra Zanotti; Stefano Cardea (Chemical Engineering Transactions)
Dye abundance in industrial wastewater is emerging as a critical issue in chemical engineering, due to their harmful impact on natural ecosystems equilibrium. Adsorption is a cost-effective and flexible unit operation to perform: however, its outcomes rely on the choice of the sorbent. Indeed, the adsorbent should expose large surface areas, to optimize the performance-to-size ratio; it should be selective, and affine with the molecule to remove from the sludge. Moreover, it should be low-cost and biodegradable. Cellulose meets these last requirements: in this work, it has been processed by supercritical drying, in order to improve network interconnectivity and enhance active sites availability. The present research focuses on the efficacy of microcrystalline cellulose on removing different dyes, as well as the effect of supercritical drying operating conditions on adsorption performances, as well as. The present study outlined that the lower the carbon dioxide density is, the more likely is for the adsorption to worsen. Moreover, pristine cellulose results to be affine with cationic dyes, rather than anionic; on the other hand, adsorption is less favourable for linear molecules rather than more compact ones.